Avoidance of reproductive conflict and the evolution of menopause in chimpanzees - Lauren C. White; Dieter Lukas; Kevin E. Langergraber; Linda Vigilant (Royal Society Open Science)
The reproductive conflict hypothesis suggests menopause is rare in nature because it is only evolutionarily favoured in specific dispersal and mating systems. In social groups with local mating, shared resource competition and female-biased dispersal, an increase in a breeding female’s relatedness to her fellow community members with age is expected to favour late-life reproductive cessation as a response to intergenerational reproductive competition. Here, we use observational and genomic data from the Ngogo chimpanzee community to characterize kinship dynamics and investigate the potential role of reproductive conflict in explaining a recent report of menopause in this community. We first find that, as predicted by simple models, the combination of female dispersal and local breeding leads to age-specific increases in relatedness between female and male community members. Next, we use the observed kinship dynamics in inclusive fitness formulae to test whether reproductive cessation might have been selected for in chimpanzee females. We find that kinship dynamics measured within subgroups of the community, where competition is presumably most intense, favour the evolution of menopause beginning around age 40. This is consistent with patterns of age-related fertility declines observed in Ngogo, suggesting reproductive conflict may have contributed to the evolution of chimpanzee post-reproductive lifespans.